Purpose as a predictor of satisfaction across relationship domains during the first semester of university. (March 2022) - Pfund, Gabrielle N.; Bono, Timothy J.; Hill, Patrick L.
Background: Sense of purpose, or the extent to which one perceives their lives to have meaningful goals and directions, may aid in initiating satisfying and stable new connections while positively maintaining old ones for college students. Purpose: The current study sought to evaluate how a college students' sense of purpose during their first week of college may predict their satisfaction with different relationship types throughout their first semester of university. Research Design: At the beginning of the semester, students reported their sense of purpose, and every week of the semester they reported their weekly relationship satisfaction across a variety of domains (i.e., parents, home friends, university friends, roommates, resident assistants, and significant others). Study Sample: The current study followed-up first year college students ( n  = 364) from a private Midwestern university who all participated in the same Psychology of Young Adulthood class. Data Analysis: Multilevel models were conducted to evaluate mean-level relationship satisfaction trajectories throughout the first semester and whether sense of purpose predicted those trajectories when accounting for gender and the Big Five personality traits. Results: Friendships with home friends and university friends as well as parental relationships increased in satisfaction during the first semester, while relationships with roommates and resident assistants decreased. Furthermore, a higher sense of purpose was associated with greater relationship satisfaction with university friends and parents, even when accounting for the Big Five personality traits, as well as greater relationship satisfaction stability. Conclusions:   Findings paint a nuanced and equivocal nature of relationships during the first semester, and point to the need to better understand how and when sense of purpose does or does not yield positive relationships over time.